Delphi developed syllabus for the medical specialty of sport and exercise medicine: part 2. Issue 2 (24th September 2020) - Humphries, David; Jaques, Rod; Dijkstra, H Paul; Asif, Irfan; Batt, Mark E; Borjesson, Mats; Ergen, Emin; Geertsema, Celeste; Gojanovic, Boris; Ionescu, Anca; Janse van Rensburg, Dina Christina; Lebrun, Constance; et al.
Abstract : Training in the medical specialty of sport and exercise medicine (SEM) is available in many, but not all countries. In 2015, an independent Delphi group, the International Syllabus in Sport and Exercise Medicine Group (ISSEMG), was formed to create a basic syllabus for this medical specialty. The group provided the first part of this syllabus, by identifying 11 domains and a total of 80 general learning areas for the specialty, in December 2017. The next step in this process, and the aim of this paper was to determine the specific learning areas for each of the 80 general learning areas. A group of 26 physicians with a range of primary medical specialty qualifications including, Sport and Exercise Medicine, Family Medicine, Internal Medicine, Cardiology, Rheumatology and Anaesthetics were invited to participate in a multiple round online Delphi study to develop specific learning areas for each of the previously published general learning areas. All invitees have extensive clinical experience in the broader sports medicine field, and in one or more components of sports medicine governance at national and/or international level. SEM, Family Medicine, Internal Medicine, Cardiology, Rheumatology and Anaesthetics were invited to participate in a multiple round online Delphi study to develop specific learning areas for each of the previously published general learning areas. All invitees have extensive clinical experience in the broader sports medicine field, and in one or more components of sports medicine governance at national and/or international level. The hierarchical syllabus developed by the ISSEMG provides a useful resource in the planning, development and delivery of specialist training programmes in the medical specialty of SEM.